Antifungal Activity of Endophytic Bacteria isolated from Pegagan (Centella asiatica L.) for Inhibition the Growth of Malassezia furfur - Vivi Yanthi; Mahyarudin Mahyarudin; Ambar Rialita (Jurnal Biologi Universitas Andalas, 2022)
Pityriasis versicolor is a superficial fungal infection characterized by changes in skin pigment due to stratum corneum colonization by Malassezia furfur. The Increasing of antifungal resistance and high recurrence rate, requires alternative treatment of medicinal plants. Pegagan (Centella asiatica L.) is known to produce secondary metabolites that have antifungal activity produced by endophytic bacteria that live on pegagan plant tissue. The study aimed to determine the antifungal activity of pegagan endophytic bacteria isolates to Inhibit the Growth of Malassezia furfur. The endophytic bacteria isolates were re cultured on NA media with a streak plate method. Antifungal activity test used the disk diffusion method which is characterized by the formation of inhibitory zones. Total of 37 endophytic bacteria isolates were successed re cultured, and there were 15 endophytic bacterial isolates that have potentcy as antifungal agent with inhibitory zones ranged from 6.5 to 15.52 mm. The most potential isolate was similarity with genus Pseudomonas. The secondary metabolites contained of alkaloids, terpenoids and saponins. The potential Centella asiatica endophytic bacteria had antifungal activity and similarity with the genus Pseudomonas.